Correlation Between Expressive Language Ability and Early Literacy in Preschool Children: A Study At Kanisius Semanggi Kindergarten - Rahmadani, Karinda Kurnia; Setyawan, Dodiet Aditya; Tirtawati , Dewi (Jurnal Penelitian Inovatif, 2025)
Early childhood is a critical period for language development, particularly in expressive language skills and early literacy. Understanding the correlation between these skills is essential for enhancing language acquisition in preschool education. This study examines the correlation between word-level expressive language ability and early literacy in preschool children at Kanisius Semanggi Kindergarten. A cross-sectional quantitative approach was employed with a total sampling method involving 50 respondents. Data were analyzed using the Kendall Tau correlation test. The study found a significant positive correla-tion (p = 0.000, r = 0.818) between expressive language ability and early literacy. Children with higher expressive language skills demonstrated superior literacy abilities.The findings highlight the importance of fostering expressive language skills in early education to improve literacy outcomes. Future research should explore intervention strategies for children with lower expressive language abilities